Determinants of Neighborhood References, and Environmental Stimuli on Purchasing Decisions for Halal Products for Consumers - Muh. Haerdiansyah Syahnur; Andi Faisal Bahari (Manunggal Halim Jaya, 2023)
This study aims to determine the effect of surrounding reference variables, namely (product, service, and brand image) and Environmental Stimuli, on purchasing decisions. This research approach uses quantitative research. The data used in this study are primary data obtained from questionnaires and secondary data. This research was conducted at Chocholicious Cake Shop Makassar City. The population in the study used the Infinite population, with a sample size of 200 respondents / people in Makassar City. Data analysis using validity test, reliability test, R-Square test, F-Square test, direct effect test, and hypothesis submission using Partial Least Square. The results of this study indicate that the variables in the surrounding reference have a positive and significant effect on the consumer purchasing decision variable; Ambient references are factors around consumers that can influence their perceptions and purchasing decisions. Which means that factors such as recommendations from friends and family, public opinion, and advertising can influence consumer purchasing decisions. Likewise, the environmental stimuli variable has a positive and significant effect on consumer purchasing decisions. Environmental stimuli are factors around consumers that can influence their perceptions and purchasing decisions, which means that factors such as store layout, product design, store atmosphere, etc. can influence consumers' purchasing decisions.